Novel Echocardiographic Parameter Assessing Pulmonary Vascular Resistance in Patient with Acyanotic Congenital Heart Disease - Muhammad Raihan Ramadhan Natadikarta; Charlotte Johanna Cool; Achmad Fitrah Khalid; Norman Sukmadi; Januar Wibawa Martha (Majalah Kardiologi Indonesia)
Background